COMPARISON OF VARIABLES RELATED TO ANTHROPOMETRIC BMI AND WHR ADULTS IN DIFFERENT AGE GROUPS (Fiep Bulletin - online, 2014)
Introduction: The Body Mass Index (BMI) and waist to hip ratio (WHR) are often used to assess the nutritional status and risk of morbidity and mortality from cardiovascular disease. Objective: To compare the rates of BMI and WHR in adults of different ages. Methodology: This was a descriptive cross-sectional study. The sample consisted of 48 subjects, 11 males and 37 females , both students IFPR Campus Palmas / PR, aged 17 to 58 years (mean = 34,02 ± 9,53). The evaluation was performed by anthropometry,  and included HR, weight, height, abdomen, hip, BMI and WHR. Three age groups were established for analysis: Group 1 - 17 to 25 years (n = 9), Group 2 - 26 to 35 years (n = 20) and Group 3 - 36 or older (n = 19). Multiple comparisons were conducted between the variables, using the Student's t and as a post hoc Tukey test. Results: No significant difference (p < 0,05) between age groups in FC and height variables between any of the age groups. Likewise, no difference between groups 2 and 3 was observed in any variable. Group 1 showed a statistically significant difference compared to groups 2 and 3, the variables weight, abdomen, hip, BMI and WHR , as seen in Figure 01. A strong correlation between age, BMI and WHR, as seen in Figure 02. Conclusion: BMI is an excellent mechanism for diagnosing nutritional status, as well as the WHR is an important tool to suggest the risk of mortality. Increasing age appears to be crucial for the expansion of anthropometric dimensions and, consequently, the risk of mortality.
Keywords: BMI; WHR; Indicators of body fat; Mortality risk.